Escherichia coli (Lilly) and Saccharomyces cerevisiae (Novo) rDNA Glucagon: An Assessment of Their Actions When Supplied Selectively to Periportal Cells in the Bivascularly Perfused Rat Liver - Lívia Bracht; Jorgete Constantin; Rosane Marina Peralta; Adelar Bracht (MDPI AG, 2023)
The actions of Eli Lilly-rDNA glucagon and Novo Nordisk-rDNA glucagon on glycogen catabolism and related parameters were investigated using the bivascularly perfused rat liver. The technique allows glucagon to be supplied to a selective portion of the hepatic periportal region (≈39%) when the former is infused into the hepatic artery in retrograde perfusion. Both glucagon preparations were equally effective in influencing metabolism (glucose output, glycolysis and O2 uptake) when supplied to all cells along the liver sinusoids. When only a selective periportal region of the liver was supplied with the hormone, however, the action of Novo Nordisk-rDNA glucagon was proportional to the accessible cell space, whereas the action of Eli Lilly-rDNA glucagon greatly exceeded the action that was expected for the accessible space. Chromatographically, both rDNA preparations were not pure, but their impurities were not the same. The impurities in Eli Lilly-rDNA glucagon resembled those found in the similarly acting pancreatic Eli Lilly glucagon. It was concluded that the space-extrapolating action of Eli Lilly-rDNA glucagon is caused by a yet-to-be-identified impurity. The hypothesis was raised that an impurity in certain glucagon preparations can enhance cell-to-cell propagation of the glucagon signal, possibly via gap junctional communication.